(untitled) (Journal of Asian Development Studies, 2014)
This current research sought to study a model of empowerment in a Malaysian sample of research universities’ academicians by investigating how psychological empowerment could mediate the relationship between structural empowerment and attitudes related to work, particularly organizational commitment. To test this relationship a cross-sectional survey with self-reported questionnaires was conducted. Cluster random sampling was used to generate a randomly selected sample of 400 academic staff in four research universities in Malaysia. A total of 260 valid questionnaires were returned, yielding a response rate of 65%. The confirmatory factor analysis including all hypothesized variables provided an adequate fit. The model fit indices indicated good mode: fit χ²/df = 2.316; CFI = .937; TFI = .937; GFI = .918; RMSEA = .051. The result of structural measurement indicated that psychological empowerment partially mediates the relationship between structural empowerment and organizational commitment. Psychological empowerment mediating the relationship between structural empowerment and organizational commitment emerged as an important factor. Structurally empowered universities which practice psychological empowerment skills are provided with another tool by which leaders can work to enhance the level of organizational commitment of their academics.